68.2k views
0 votes
Solve for y: 88x - 67y = 756

User Max Markov
by
5.3k points

1 Answer

6 votes

The given equation is


88x-67y=756

To solve for y, we need to isolate y on one side and the other 2 terms on the other side

To do that we will subtract both sides by 88x


\begin{gathered} 88x-88x-67y=756-88x \\ -67y=756-88x \end{gathered}

We need to make the coefficient of y = 1, then we will divide both sides by -67


\begin{gathered} (-67y)/(-67)=(756)/(-67)-(88x)/(-67) \\ \\ y=-(756)/(67)+(88)/(67)x \\ \\ y=(88)/(67)x-(756)/(67) \end{gathered}

The answer is


y=(88)/(67)x-(756)/(67)

User Vladimir Gadzhov
by
5.0k points